2004
DOI: 10.1021/om034240+
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity Differences in the Syntheses of Chelating N-Heterocyclic Carbene Complexes of Rhodium Are Ascribed to Ligand Anisotropy

Abstract: Chelating bis(imidazolium) salts having (CH 2 ) n chains of different lengths (n ) 1-4) linking the diazole rings show very large reactivity differences on metalation with [(cod)RhCl] 2 . Long linkers favor a square-planar Rh(I) product, while short linkers favor octahedral Rh(III). We ascribe the origin of the effect to the restricted rotation of the highly sterically anisotropic diazole rings and the different preferred orientations of these rings as n changes. Defining the x and y axes as the Rh-carbene bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
170
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(188 citation statements)
references
References 28 publications
14
170
0
2
Order By: Relevance
“…[8] Furthermore, palladium complexes of the type Pd(pyridine)Cl 2 (NHC) and PdCl 2 (NHC) 2 have been found to exhibit potent anticancer activity. [9] Various bis-NHC ligands have been reported, which are usually linked by alkenic chains [7,[10][11][12][13] or an N-donor such as a pyridyl derivative or amine, [14][15][16] and tend to form chelating complexes with metals. NHC ligands containing a xylylene-bridge are surprisingly rare.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Furthermore, palladium complexes of the type Pd(pyridine)Cl 2 (NHC) and PdCl 2 (NHC) 2 have been found to exhibit potent anticancer activity. [9] Various bis-NHC ligands have been reported, which are usually linked by alkenic chains [7,[10][11][12][13] or an N-donor such as a pyridyl derivative or amine, [14][15][16] and tend to form chelating complexes with metals. NHC ligands containing a xylylene-bridge are surprisingly rare.…”
Section: Introductionmentioning
confidence: 99%
“…While HPLC-MS analysis suggests a pure compound, NMR spectroscopic analysis shows two distinct sets of signals that were attributed to the rac and meso diastereoisomers of 5 as a consequence of the chirality of the complex at each ruthenium center. [15,24] Solubility tests revealed that one of the two isomers is less soluble in MeCN and was thus successfully separated by repetitive precipitation and filtration. This isomer is stable in solution over several days, which demonstrates that racemization at ruthenium is very slow.…”
mentioning
confidence: 99%
“…6, 17 The reaction 20 was carried out with 3b in order to avoid a potential mixture of Cl and I on the Rh and Ru centres. It was conducted in the presence of excess Ag 2 O in dichloromethane at reflux.…”
mentioning
confidence: 99%